Mongolia : Statistical Annex. (IMF Staff Country Reports; Country Report ;, 2000)
This report provides the details of the IMF's projections and estimates for Mongolia on selected economic indicators, 1995-98; gross domestic product; output of major agricultural products and basic industrial and mining products; petroleum balances; electricity sector; retail prices; summary operations of the general government; general government revenue, expenditure, expenditure by function and social expenditure; official grants; balance of payments, 1994-98; budgetary support for enterprises; services and income tax accounts, 1996-98; trade regime; monetary survey; interest rates; balance sheet of the bank of Mongolia; consolidated balance sheet of commercial banks, 1996-99, and so on.